Assessment of Metoprolol-Induced Liver Injury and Vitamin E’s Hepatoprotective Role in Rabbits - Maysaa Banay Zubairi (Pharmaceutical Research: Recent Advances and Trends Vol. 5, 2024)
Background: Drug-induced liver injury is a well-known adverse effect of numerous medications, with clinical presentation ranging from an elevation of asymptomatic liver enzymes to liver failure. Metoprolol has been linked to some clinical cases of drug-induced liver injury, with the first case report of metoprolol hepatotoxicity being reported in 1989. Objective: This study aims to investigate the hepatotoxicity of metoprolol and find a prophylactic way to protect the liver through the use of Vitamin E. Methods: A total of 18 male rabbits were divided randomly into three groups, with six in each group. An accurate dose of 20 mg/kg was administered orally for each rabbit through a stainless-steel feeding tube. Group I (control) received corn oil, Group II was treated with metoprolol (20 mg/kg), and Group III was treated with Vitamin E (175 mg/kg) 30 min before metoprolol treatment. All treatments were given orally and daily for 14 days; animals were sacrificed on day 15. Biochemical parameters were estimated, and the liver was used for histopathological examinations. The data were statistically evaluated using ordinary one-way analysis of variance followed by Tukey’s multiple comparisons test using GraphPad Prism 8 computer software. Results: The results of the current study revealed that metoprolol (20 mg/kg/d for 14 days) caused lipid peroxidation, significant elevation in the serum liver enzymes, and histopathological changes in the liver. Histopathological changes of liver injury were found in all metoprolol-treated rabbits, while these changes were minimized in all rabbits who were given Vitamin E. Serum liver function tests and malondialdehyde (MDA) were significantly elevated after metoprolol treatment and returned close to the control value on prior treatment with Vitamin E. Serum MDA, aspartate aminotransferase, and alanine aminotransferase were significantly decreased following treatment with Vitamin E. Conclusion: Vitamin E may have a hepatoprotective effect against metoprolol-induced liver injury in rabbits.